Toward Efficient Geolocation in SAGIN: A Single-Satellite Geolocation Method Combined with Bandlimited Signal Extrapolation. Issue 1 (1st November 2022) - Zhang, Yusi; Sha, Xuejun; Li, Yong; Lin, Xu
Abstract : The satellite network, as an essential part of space-air-ground integrated network (SAGIN) with high coverage and mobility, not only expects a promising development but faces increasing interference and tenser satellite spectrum resources. The geolocation function of single satellite is widely used in the low-orbit satellite network but limited to the long measuring duration, which cannot adapt the flexiblity in SAGIN scenario. In this paper, an efficient single satellite geolocation method is proposed combined with bandlimited signal extrapolation in order to save more operation time and ensure the positioning accuracy. Due to the bandlimited characteristic of the radiated signal, information received from the satellite can be further extrapolated so that more doppler frequency values are obtained. The estimated accuracy can be improved with the extra information input to grid search method. Besides, short-term single-satellite geolocation can be realized to meet the higher efficiency requirement of SAGIN. Simulation results demonstrate the superiority of the proposed method in terms of the positioning accuracy compared to the geolocation method without extrapolation.